Randomized Controlled Trial of Herbal Extracts (Eugenia polyantha, Apium graveolens, Nigella sativa) and Allopurinol Effect on Serum Uric Acid, Urinary Uric Acid and High Sensitivity C-Reactive Protein Levels in Subject with Hyperuricemia - Bantar Sutoko; Rakhma Yanti Hellmi; Ika Vemillia W; Stepanus Agung L (Indonesian Journal of Rheumatology, 2019)
Background: Eugenia polyantha, Apium graveolens, and Nigella sativa are extracts which in preclinical trial can reduce uric acid serum, increase urinary uric acid excretion. Allopurinol is an inhibitor of the xanthine oxidase enzyme which can also reduce the increase of hsCRP in subjetcs with hyperuricemia. Objective: To determine the safety and effect of herbal extracts in reducing serum uric acid, increasing uric acid excretion and reducing hsCRP levels in patients with hyperuricemia compared with allopurinol. Method: This study was a double blind randomized controlled trial (RCT). The subjects were hyperuricemic patients aged ³18 years. The subject was divided into groups that received 3000 mg/day of herbal extracts and allopurinol 100 mg/day for 4 weeks. Evaluation of serum uric acid and urinary uric acid urine were every week, and hsCRP levels was baseline and end of intervention. Other parameters related to the safety of use were examined every 2 weeks. Results: A number of 44 hyperucemia subjects, 23 subjects received herbal extracts and 21 subjects received allopurinol. The decrease of uric acid serum levels in the herbal extract group was 0,467±1,123;0,600;-2,70-3,00 (p=0.027), while in the allopurinol group 1,11 4±0,813;1,30;-1,30-2,30 (p=0,000). Uric acid excretion in the herbal extract group decrease 71,00±1,970;5,50;-92,00-702,00 (p=0,269) and in the allopurinol group decrease 64,54±1,298;22,00;-29,00-440,0 (p=0.003). The reduction of hsCRP in the herbal extract group was 0.08±0.639; 0.01; -1.55-2.05 (p=0.658), and the allopurinol group was -0.33 ± 0.806; -0.01; -2.73- 0.31 (p=0.256). Conclusion: Herbal extracts (Eugenia poliantha, Apium graveolens and Nigella sativa) and allopurinol can reduce serum uric acid levels in patients with hyperuricemia. Allopurinol also can reduce urinary uric acid excretion.